2013
DOI: 10.1007/s13105-013-0302-3
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damage and alterations in antioxidant enzyme activities in the kidneys of rat exposed to trichloroacetic acid: protective role of date palm fruit

Abstract: In this study, we investigated the antioxidant and protective properties of date fruit aqueous extract (DFAE) on trichloroacetic acid (TCA)-induced nephrotoxicity in rat. Oral administration of TCA as drinking water (0.5 and 2 g/L) daily for 2 months caused nephrotoxicity as evident by elevated levels of plasma creatinine, urea, and uric acid. Activity of antioxidant enzymes, catalase (CAT) and glutathione peroxidase (GPx), was decreased, whereas superoxide dismutase (SOD) activity and malondialdehyde (MDA) le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…GSH is a tripeptide low molecular weight protein that plays a fundamental role in detoxifying drugs and toxins, metabolism and regulation of various pathways to maintain homeostasis. We found that exposure to TCE led to decreased GSH in a dose-dependent manner that is in agreement with other studies ( 12 , 24 , 29 , 30 ). Our data showed that vitamin E enhanced GSH level in TCE treated rats and protected kidney against TCE-induced oxidative stress.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…GSH is a tripeptide low molecular weight protein that plays a fundamental role in detoxifying drugs and toxins, metabolism and regulation of various pathways to maintain homeostasis. We found that exposure to TCE led to decreased GSH in a dose-dependent manner that is in agreement with other studies ( 12 , 24 , 29 , 30 ). Our data showed that vitamin E enhanced GSH level in TCE treated rats and protected kidney against TCE-induced oxidative stress.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the TCE-treated rats showed a significant increase in the MDA level in a dose-dependent manner. In agreement with this finding, TCE has been shown to increase the level of MDA ( 24 , 25 , 29 , 30 ) Our data showed vitamin E attenuated MDA level . Our finding suggested that vitamin E has potential to protect kidney against TCE induced lipid peroxidation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A number of in vitro and in vivo studies have been performed to substantiate their use in folk medicine [1,2]. Date extracts were shown to possess a myriad of pharmacological properties such as antioxidant [3], anti-inflammatory [4], antiatherogenic [5], hepatoprotective [6], anticancer [6], nephroprotective [7], antimicrobial [8], antiallergic [9], immunostimulatory [10], neuroprotective [11], antifungal [12], antimutagenic [13] and gastrointestinal transition stimulatory activity [14]. Date supplementation was shown to be beneficial in Alzheimer's disease transgenic mice model [15].…”
Section: Introductionmentioning
confidence: 99%
“…The overall findings of this study suggest that INH presents a circadian variation in renal toxicity dependent on dosing-time. This must be considered when this medication is administered to patients to manage INH toxic effects [50,51].…”
mentioning
confidence: 99%